PENGARUH PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN SERTA HASIL KACANG HIJAU (Vigna radiata L .) DAN JAGUNG SEMI (BABY CORN) PADA POLA TUMPANGSARI - Yohanes Mulatua; Armaini Armaini Armaini; Ardian Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The objective of this research is to determine the effect of giving dosage Biofertilizer Liquid on growth and production, and to determine the best Biofertilizer Liquid dosage in intercropping systems of green beans and baby corn. This research was conducted at experimental station of the Faculty of Agriculture, Riau University. This research was conducted experimentally using a Completely Randomized Design consisting of six treatments and three replications to obtain 18 experimental units. The treatment in this study was the dosage of NASA Biofertilizer Liquid 5, ha-1, 10 l.ha-1, 15 l.ha-1, 20 l.ha-1, 25 l.ha-1, 30 l.ha-1. The observed parameters on green beans were plant height (cm), stem diameter (mm), number of pods per plant (fruit), production per plot (g), weight of 1000 dry seeds (g), on baby corn is plant height (cm ), age of harvest (HST), diameter of baby corn without cornhusk (cm), length of baby corn without cornhusk (cm), weight of baby corn without cornhusk per plot (g). The data obtained were analyzed by variance and tested further with Duncan's new range test at the level of 5%. The results showed that the application of NASA Biofertilizer Liquid with dosage significantly affected the observed parameters. The results showed of Biofertilizer Liquid NASA at dosage of 25 l.ha-1-30 l.ha-1 is the best dosage in increasing growth and the result of green beans intercropped with baby corn Kata Kunci:   Kacang Hijau, Jagung Semi, POC NASA, Tumpangsari